Teacher Digital Competency and Pedagogical Innovation in Hybrid Classrooms - Badri Munawar; Rihatul Jannah (Journal of Educational Technology Innovation and Applications, 2025)
The rise of hybrid learning environments necessitates a reexamination of teacher competencies in digital pedagogy. As education systems integrate both face-to-face and online instruction, the ability of teachers to effectively use digital tools while maintaining pedagogical coherence becomes increasingly vital. This article explores the relationship between teacher digital competency and pedagogical innovation in hybrid classrooms. Adopting a conceptual and literature-supported opinion approach, the study presents a framework outlining key digital competencies and their influence on innovative pedagogical practices. The results and discussion focus on three critical areas: instructional design, technology-enhanced interaction, and assessment adaptability. Each section is supported by empirical insights and tabular analyses. The article concludes with recommendations for professional development and institutional support to strengthen teacher readiness for hybrid teaching.